Endothelial BMPR2 Loss Drives a Proliferative Response to BMP (Bone Morphogenetic Protein) 9 via Prolonged Canonical Signaling - Theilmann, Anne L.; Hawke, Lindsey G.; Hilton, L. Rhiannon; Whitford, Mara K.M.; Cole, Devon V.; Mackeil, Jodi L.; Dunham-Snary, Kimberly J.; Mewburn, Jeffrey; James, Paula D.; Maurice, Donald H.; Archer, Stephen L.; Ormiston, Mark L. (Arteriosclerosis, thrombosis, and vascular biology, 2020)
OBJECTIVE:Pulmonary arterial hypertension is a disease of proliferative vascular occlusion that is strongly linked to mutations in BMPR2—the gene encoding the BMPR-II (BMP [bone morphogenetic protein] type II receptor). The endothelial-selective BMPR-II ligand, BMP9, reverses disease in animal models of pulmonary arterial hypertension and suppresses the proliferation of healthy endothelial cells. However, the impact of BMPR2 loss on the antiproliferative actions of BMP9 has yet to be assessed. APPROACH AND RESULTS:BMP9 suppressed proliferation in blood outgrowth endothelial cells from healthy control subjects but increased proliferation in blood outgrowth endothelial cells from pulmonary arterial hypertension patients with BMPR2 mutations. This shift from growth suppression to enhanced proliferation was recapitulated in control human pulmonary artery endothelial cells following siRNA-mediated BMPR2 silencing, as well as in mouse pulmonary endothelial cells isolated from endothelial-conditional Bmpr2 knockout mice (Bmpr2). BMP9-induced proliferation was not attributable to altered metabolic activity or elevated TGFβ (transforming growth factor beta) signaling but was linked to the prolonged induction of the canonical BMP target ID1 in the context of BMPR2 loss. In vivo, daily BMP9 administration to neonatal mice impaired both retinal and lung vascular patterning in control mice (Bmpr2) but had no measurable effect on mice bearing a heterozygous endothelial Bmpr2 deletion (Bmpr2) and caused excessive angiogenesis in both vascular beds for Bmpr2 mice. CONCLUSIONS:BMPR2 loss reverses the endothelial response to BMP9, causing enhanced proliferation. This finding has potential implications for the proposed translation of BMP9 as a treatment for pulmonary arterial hypertension and suggests the need for focused patient selection in clinical trials. GRAPHIC ABSTRACT:A graphic abstract is available for this article.